Predicting bite force and cranial biomechanics in the largest fossil rodent using finite element analysis - Cox, Philip G (J Anat, 2015)
Josephoartigasia monesi, from the Pliocene of Uruguay, is the largest known fossil rodent, with an estimated body mass of 1000 kg. In this study, finite element analysis was used to estimate the maximum bite force that J. monesi could generate at the incisors and the cheek teeth. Owing to uncertainty in the model inputs, a sensitivity study was conducted in which the muscle forces and orientations were sequentially altered. This enabled conclusions to be drawn on the function of some of the masticatory muscles. It was found that J. monesi had a bite of 1389 N at the incisors, rising to 4165 N at the third molar. Varying muscle forces by 20% and orientations by 10° around the medio-lateral aspect led to an error in bite force of under 35% at each tooth. Predicted stresses across the skull were only minimally affected by changes to muscle forces and orientations, but revealed a reasonable safety factor in the strength of the skull. These results, combined with previous work, lead us to speculate that J. monesi was behaving in an elephant-like manner, using its incisors like tusks, and processing tough vegetation with large bite forces at the cheek teeth.